Efficacy of bifidobacterium-related preparations on depression: the first meta-analysis - Huang, Ruihan; Liu, Yongsheng (Frontiers in Psychiatry, 2024)
Currently, depression-induced suicide has emerged as the primary contributor to the worldwide burden of disability(Monroe and Harkness 2022). However, the prevailing drug treatment not only suffers from delayed effectiveness and limited efficacy, but also there are withdrawal symptoms and rebound phenomenon (Henssler et al. 2019;Dilsaver and Greden 1984;Horowitz et al. 2023).Consequently, there is an imperative to investigate safer and more efficient treatments to ameliorate the clinical manifestations of depression. At present, there is increased evidence that probiotics can improve the symptoms of depression, but the existing studies use many and mixed types of probiotics (Chudzik et al. 2021;Liu, Walsh, and Sheehan 2019), and it is impossible to determine the specific efficacy of bifidobacteria in the treatment of depression. This review will systematically review the effects of bifidobacteria on the treatment effect of depression, Meta-analysis showed that Bifidobacterium-related preparations effectively improved depressive symptoms in patients with depression.This study represents the initial meta-analysis conducted on the use of bifidobacteria-related agents for treating depression. The objective was to determine the effect of bifidobacteria-related preparations on improving depressive symptoms.We found that Bifidobacterium and its related agents can effectively reduce depression scale scores in patients with depression, suggesting the need for further research into this potential strategy for the prevention and treatment of depression.